2018
DOI: 10.1109/trpms.2018.2831208
|View full text |Cite
|
Sign up to set email alerts
|

Simulations of a Multipinhole SPECT Collimator for Clinical Dopamine Transporter (DAT) Imaging

Abstract: SPECT imaging of the dopamine transporter (DAT) is used for diagnosis and monitoring progression of Parkinson’s Disease (PD), and differentiation of PD from other neurological disorders. The diagnosis is based on the DAT binding in the caudate and putamen structures in the striatum. We previously proposed a relatively inexpensive method to improve the detection and quantification of these structures for dual-head SPECT by replacing one of the fan-beam collimators with a specially designed multi-pinhole (MPH) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Finally, as we mentioned earlier, our proposed system has approximately 2–3.3 times reduction in scan time, up to 1.7 times improved volume sensitivity and reasonable spatial resolution for a brain study when compared to the conventional dual‐head scanner. However, if we compare our proposed scanner with an experimental dedicated multi‐pinhole brain SPECT system, 47,48 the dedicated system has good spatial resolution (~4.8 mm FWHM in the center of the cylindrical volume of interest) and the caudate and putamen in the brain phantom are well differentiated due to the magnification of the pinhole collimator for a small spherical volume having a 21 cm‐diameter. In addition, the investigational multi‐pinhole dedicated brain SPECT (e.g., G‐SPECT) having a high spatial resolution (below 3 mm) and a high sensitivity of 415 cps/MBq takes only 30 s for a total brain perfusion scan with optimized bed position sequences 49,50 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, as we mentioned earlier, our proposed system has approximately 2–3.3 times reduction in scan time, up to 1.7 times improved volume sensitivity and reasonable spatial resolution for a brain study when compared to the conventional dual‐head scanner. However, if we compare our proposed scanner with an experimental dedicated multi‐pinhole brain SPECT system, 47,48 the dedicated system has good spatial resolution (~4.8 mm FWHM in the center of the cylindrical volume of interest) and the caudate and putamen in the brain phantom are well differentiated due to the magnification of the pinhole collimator for a small spherical volume having a 21 cm‐diameter. In addition, the investigational multi‐pinhole dedicated brain SPECT (e.g., G‐SPECT) having a high spatial resolution (below 3 mm) and a high sensitivity of 415 cps/MBq takes only 30 s for a total brain perfusion scan with optimized bed position sequences 49,50 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the investigational multi‐pinhole dedicated brain SPECT (e.g., G‐SPECT) having a high spatial resolution (below 3 mm) and a high sensitivity of 415 cps/MBq takes only 30 s for a total brain perfusion scan with optimized bed position sequences 49,50 . However, these dedicated brain designs using multi‐pinhole collimators have a significant limitation as for general‐purpose imaging scenarios (e.g., bone SPECT) due to a small cylindrical volume of interest 48 . In contrast, our proposed detector head geometry could be radially extended and still could have shorter scan time by swiveling individual detectors, which will be further investigated to optimize the acquisition mode with a slightly common axis of rotation if needed.…”
Section: Discussionmentioning
confidence: 99%
“…Cone-beam and fanbeam collimators were used to make better usage of the detector area than parallel-hole collimators when imaging a structure such as the head which is of smaller area than the detector, thereby improving the sensitivity / spatial resolution trade-off for imaging [20,21]. More recently, studies have shown that customized multi-pinhole collimators may further enhance the performance of the existing clinical generalpurpose SPECT systems for brain imaging [22][23][24][25][26].…”
mentioning
confidence: 99%
“…King and co-workers proposed a combination of a MPH collimator on one head of a double-head SPECT system and a fan-beam collimator on the other head (King et al, 2016). The rationale was that the MPH collimator would provide high resolution of 4.8 mm (Konik et al, 2018) and high sensitivity for imaging of the interior portion of the brain, particularly the striatum. The fan-beam collimator would provide lower resolution, but complete sampling of the brain addressing data sufficiency and allowing a volume-of-interest to be defined over cortical brain reference regions for semi-quantitative analysis (King et al, 2016).…”
Section: Accepted Manuscript Discussionmentioning
confidence: 99%